THE EFFECT OF LEVERAGE, LIQUIDITY AND RECEIVABLE TURNOVER ON PROFITABILITY IN MANUFACTURING COMPANIES IN THE GOODS AND CONSUMPTION SECTOR LISTED ON THE IDX 2016-2020 - ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine whether the variables of leverage, liquidity and accounts receivable turnover have a positive effect on profitability. The sample selection used the Purposive Sampling technique with the number of samples used in this study were 41 companies from 65 companies listed on the Indonesia Stock Exchange in 2016- 2020. The data analysis technique used the individual parameter significant test (t test statistic). The conclusion of this study shows that the variable leverage (DAR), Liquidity (CR) does not have a positive effect on Profitability (ROA) while the Accounts Receivable Turnover (RT) variable has a positive effect on Profitability (ROA).